Cannabis in the traditional Southern Thai medical recipe. - Pussapaphan, Namon; Busabong, Witthaya (Asian Journal of Traditional and Innovative Arts and Textiles, 2022)
The study-base article in title ‘The Cannabis in the Traditional Southern Thai Medical Recipe’ which has designed on the objective to study the use of cannabis in the treatment of various diseases mentioned in ‘The 100 traditional southern recipes of Thailand’. It is the collection of local literature and folklore of The Institute for Southern Thai Studies, Thaksin University. The book was studied as the main data and information together with all related documents; researches, studies and interviews. The interviews made with village people and traditional medicine healer or folk medicine doctor. The study found Southern Thai people know cannabis and can use cannabis as medicines and in cooking of various food recipes, from the old days until now, for a very long time. Cannabis in folk medicine usage was wild cannabis found widely in the natural environment in all provinces in the Southern region. In the recipe and formularies of folk medicine have no exact indication of cannabis part in clear information but wording opened as ‘Cannabis’. It was found various cannabis ingredient in all forms such as powder, liquid, tablet or bolus. Cannabis formularies covered diseases and group of symptoms and the most found included; Fainting, Dizziness, Ague and Hemorrhoids, etc. It can be concluded that the use of cannabis in the Southern Thailand is local wisdom. It has been transferred from generation to generation for a long time and this wisdom is also recorded in the folk medicine document called ‘Nang Sue But’. Cannabis formularies and recipes are ensured its properties and effectiveness in the treatment of diseases by the long time recording folk documents.